Chuantong-shehui-moqi-Huabei-de-shengtai-yu-shehui - Wang, Jiange 1964- (Shenghuo, Dushu, Xinzhi Sanlian Shudian, 2009)
Inh.:
PST: Ecological environment and society in North China (1500 - 1950). - In chines. Schr. - Inh.-Verz. auch in engl. Sprache
Includes bibliographical references
Keywords: Geschichte 1500-1950; Ecology / China; Social change / China; Ökologie; Ökosystem; Gesellschaft; China -- Nord